2019
DOI: 10.3389/fgene.2019.00815
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Prognostic Value of Selected MicroRNAs in Luminal Breast Cancer

Abstract: Breast cancer (BrC) is the most frequent malignancy and the leading cause of cancer death among women worldwide. Approximately 70% of BrC are classified as luminal-like subtype, expressing the estrogen receptor. One of the most common and effective adjuvant therapies for this BrC subtype is endocrine therapy. However, its effectiveness is limited, with relapse occurring in up to 40% of patients. Because microRNAs have been associated with several mechanisms underlying endocrine resistance and sensitivity, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 73 publications
1
29
0
Order By: Relevance
“…Regarding the evaluation of the likelihood of recurrence and resistance to therapeutics such as endocrine resistance [ 83 , 88 , 89 ], the expression of miRNAs should be tested in primary tumor sites, ideally in multicenter studies. Moreover, in vitro evaluation might contribute to the functional characterization of specific miRNAs [ 62 ]. Above all, the role of miRNA expression in liquid biopsies highlights its role as a non-invasive biomarker [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the evaluation of the likelihood of recurrence and resistance to therapeutics such as endocrine resistance [ 83 , 88 , 89 ], the expression of miRNAs should be tested in primary tumor sites, ideally in multicenter studies. Moreover, in vitro evaluation might contribute to the functional characterization of specific miRNAs [ 62 ]. Above all, the role of miRNA expression in liquid biopsies highlights its role as a non-invasive biomarker [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the analysis of 139 BC tissue samples revealed that downregulation of miR-182-5p and miR-200b-3p represents independent prognostic parameter for disease recurrence in patients with luminal BC after endocrine therapy. Decreased disease-free survival is connected with the downregulation of miR-30 family (miR-30b-5p, miR-30c-5p) [ 62 ]. On the other hand, a global miRNA screen in primary tumors of 6 matched pairs of ER-positive, postmenopausal BC patients treated with tamoxifen (either recurrence-free or developed a recurrence) suggested that higher expression of miR-126 and miR-10a is seen in patients with longer relapse-free survival.…”
Section: Mirnas and Bc Prognosismentioning
confidence: 99%
“…MiR-138 led cells to proliferation, inhibited apoptosis in vivo, and the tumor suppressor candidate TUSC2 was shown to be a direct target of miR-138. Amorim et al [45] investigated miRNAs expression levels in 139 Luminal BC and identified a panel of four miRNAs (miR-30c-5p, 30b-5p, 182-5p, 200b-3p) as independent predictors of endocrine therapy benefits. MiR-182-5p and 200b-3p provided prognostic information about recurrence following endocrine therapy.…”
Section: Tissue Mirnas In Breast Cancer Molecular Subtypesmentioning
confidence: 99%
“…Current research on microRNAs has generally focused on their use as a diagnostic tool [14,15]. In regards to miR-96 and miR-183, a correlative relationship between these microRNAs and patient prognosis has been observed, indicating their potential use as biomarkers [16].…”
Section: Plos Onementioning
confidence: 99%